2014
DOI: 10.2217/fmb.14.35
|View full text |Cite
|
Sign up to set email alerts
|

Improved Treatment of Multidrug-Resistant Bacterial Infections: Utility of Clinical Studies

Abstract: In a time of increasing antibacterial resistance and limited availability of new antibiotics, clinical studies are much needed to assess treatment options against multidrug-resistant organisms (MDROs). In this review, we describe the clinical challenge caused by MDROs and present recent evidence on how clinical studies may generate quality data to improve antibiotic treatment of MDRO infections. To this aim, we critically assess the current status, gaps and challenges associated with observational and interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…Interestingly, however, a recent retrospective study from one center showed lower survival among patients treated with BLBLIs (13). This is an observational study, and thus, the typical limitations of this design apply, including lack of randomization, the potential effects of unmeasured variables, and residual confounding (14). Although this study has, to the best of our knowledge, the biggest sample size published to date, its statistical power is still limited and cannot exclude a potential relevant difference between carbapenems and BLBLIs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, however, a recent retrospective study from one center showed lower survival among patients treated with BLBLIs (13). This is an observational study, and thus, the typical limitations of this design apply, including lack of randomization, the potential effects of unmeasured variables, and residual confounding (14). Although this study has, to the best of our knowledge, the biggest sample size published to date, its statistical power is still limited and cannot exclude a potential relevant difference between carbapenems and BLBLIs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study has some methodological strengths, which should be taken into consideration. The hypothesis, design, and statistical analysis plan were preregistered so as to avoid casual post hoc findings, as recommended for observational studies (14,28,29). Very strict criteria for the assignment of treatments were applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations